THE IMPACT OF THE NEW PENSION POLICY OF THE FEDERAL GOVERNMENT OF NIGERIA ON EMPLOYEES AND PUBLIC SECTOR ADMINISTRATION: A STUDY OF MICHAEL OKPARA UNIVERSITY OF AGRICULTURE, UMUDIKE (2008- 2018) - Ekemam, Hillary I.; Obi, Donald Oluchukwu (African Journal of Social and Behavioural Sciences, 2021)
The study examines the Impact of the New Pension Policy of the Federal Government on Employees and on the Administration of the Nigeria Public Sector using Michael Okpara University of Agriculture, Umudike (MOUAU) as a case study. The Nigeria public service before the introduction of Pension Policy in 2004 operated an Unfunded Defined Benefit Scheme (UDBS) and the payment of retirement benefits were budgeted annually. The annual budgetary allocation made the old Scheme to be most vulnerable. The New Pension Scheme upon introduction was found to be associated with several corrupt practices, amongst which is non-release of pension funds. The study is poised to unravel the extent to which the New Pension Scheme has improved the welfare of retired personnel, amongst others. Data for the study were obtained from a combination of primary and secondary sources. Four research questions were raised and questionnaires developed using Four Point Rating Scale. The population of study comprised the entire employees of MOUAU which is 3400 with a sample size of 340. The data analysis showed that the new pension policy is properly implemented, improves the welfare of retired personnel’s, addresses the problems of corruption and guarantee minimum living standards for employees in MOUAU but still saddled with some inadequacies. like delay in payment of benefits, among others. The study recommended amongst others, that Federal Government should revisit the policy by making employees access their savings as loans while in service to solve their imminent proplems,and that government should through her agencies conduct trainings for potential retirees, increase salaries of workers to boost their retirement savings etc